Natural organic matter from the dispersion train of gold sulfide tailings: group composition and fractionation of elements: case study of Ursk Tailings, Kemerovo Region, Siberia. Issue 1 (2020) - Myagkaya, Irina N.; Saryg-ool, B.Yu.; Surkov, O.N.; Zhmodik, S.M.; Lazareva, E.V.; Taran, O.P.
No abstract available